A review on bystanders terminologies in cyberbullying - Anwar R.M.; Rahim F.A.; Victor P.A. (American Institute of Physics Inc., 2023)
Most of the communication today takes place online, thereby reflecting a significant part of our lives. Commuting from offline to online contact causes many challenges, misunderstandings, and differences, not knowing how words are interpreted in various terminologies. In terms of individuals virtually harming another individual-bully-victim scenario when online communication goes wrong, there are witnesses or bystanders who passively involved and do nothing. An upstander is a person who actively involved in the cyberbullying incident, opposes any unfair or intolerant acts, and intervenes on behalf the victims or bullies. While the research on programs to address cyberbullying is keep on increasing, only few studies focused on witness terminologies in cyberbullying. Our study aims to deeper understand the terminologies used in existing studies related to bystander behavior in cyberbullying. A systematic literature review approach was used using three databases. A total of 220 articles were extracted using a predefined search string. A specific criterion was applied to the extracted articles. A total of 99 articles were selected for further analysis. Based on the review, the bystander terminologies can be divided into Neutral, Positive and Negative. 2022 Author(s).